Base stations and wireless networks : exposures and health consequences : proceedings International Workshop, Geneva, Switzerland, 15-16 June 2005 (Geneva, 2007)
"This workshop covered issues such as the exposure from mobile phone base stations and other wireless networks, future wireless technologies, review of possible health consequences from the above, risk communication to the public related to radio base stations exposure, and response from governments and other stakeholders. The aim of the conference was to review the current state of knowledge and opinions of the conference participants and propose ways forward on this issue. The meeting was convened by the WHO International EMF Project as part of the scientific review process to determine biological and health effects from exposure to EMF. The purpose of these workshops is to bring together expert scientists so that established health effects and gaps in knowledge requiring further research can be identified."